2017
DOI: 10.1162/neco_a_00989
|View full text |Cite
|
Sign up to set email alerts
|

Dendrites Enable a Robust Mechanism for Neuronal Stimulus Selectivity

Abstract: Hearing, vision, touch -underlying all of these senses is stimulus selectivity, a robust information processing operation in which cortical neurons respond more to some stimuli than to others. Previous models assume that these neurons receive the highest weighted input from an ensemble encoding the preferred stimulus, but dendrites enable other possibilities. Non-linear dendritic processing can produce stimulus selectivity based on the spatial distribution of synapses, even if the total preferred stimulus weig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(40 reference statements)
2
8
0
Order By: Relevance
“…Our results also relate to a study 21 where we made use of dendrites to implement another computation with relevance to biology, namely direction selectivity. In the earlier study, we demonstrated how dendrites make the implementation resilient to massive synaptic failure, and this past work shows that dendrites improve the computing robustness.…”
Section: Discussionsupporting
confidence: 57%
“…Our results also relate to a study 21 where we made use of dendrites to implement another computation with relevance to biology, namely direction selectivity. In the earlier study, we demonstrated how dendrites make the implementation resilient to massive synaptic failure, and this past work shows that dendrites improve the computing robustness.…”
Section: Discussionsupporting
confidence: 57%
“…Our results also relate to a study [4] where we made use of dendrites to implement another computation with relevance to biology, namely direction selectivity. In the earlier study, we demonstrated how dendrites make the implementation resilient to massive synaptic failure, and this past work shows that dendrites improve the computing robustness.…”
Section: Discussionsupporting
confidence: 57%
“…This stimulus selectivity increases the neuron’s robustness to synaptic and dendritic failure. Using compartmental modeling they also showed how this clustered activation model is compatible with the that the mixture of selectivities in dendrites is different from the somatic selectivity (Cazé et al, 2017). Synaptic clustering may also have a functional role in the olfactory system.…”
Section: Synapse Clustering In Sensory Systemsmentioning
confidence: 79%
“…Nonlinear dendritic processing can affect the stimulus selectivity of a neuron, even if the total synaptic weight of the preferred stimulus does not exceed that of the non-preferred input. Cazé et al (2017) used computational modeling to demonstrate how this stimulus selectivity arises from the spatial distribution of synapses. This stimulus selectivity increases the neuron’s robustness to synaptic and dendritic failure.…”
Section: Synapse Clustering In Sensory Systemsmentioning
confidence: 99%